Power of Millets- Critical for addressing Ecological, Agrarian, and Emerging health crisis in Punjab - Thakur, Jarnail Singh; Kaur, Harmanjeet; Thakur, Chaitanya Devesh Singh (Indian Journal of Community Health, 2022)
The state of Punjab is facing a major threat of ecological, agrarian as well as emerging health crisis. Continuously depleting water tables due to unregulated use of irrigation water and increased cultivation of water-thirsty, varieties of rice are posing major threat to water availability in the state. Indiscriminate use of chemicals in farming leading to soil infertility, polluted surface waters and air pollution are contributing to ecological catastrophe and eventually leading to many health problems in the population. Hence there is need to focus on environmentally friendly, economically viable and health benefitting solutions. Millets as climate change compliant crops score highly over other grains in terms of marginal growing conditions and high nutritional value are proposed as a solution for emerging challenges in Punjab.